The orality in the new criminal procedure code of the argentine nation - Leonel González Postigo; Tobías José Podestá (Revista Brasileira de Direito Processual Penal, 2017)
The new Criminal Procedure Code of the Nation of Argentina established a system of oral hearings. This article describes the main changes of each stage of the process together with the identification of the challenges involved in the dynamics of the audiences.